Geomechanical, petrophysical, and mineralogical properties of limestone samples from Kansas - Osorio, Nelsy (My University, 2025)
The use of limestone in aggregate production and infrastructure projects necessitates a comprehensive investigation of its geomechanical and mineralogical properties across various scales and conditions. This study investigates the geomechanical properties, specifically Young’s Modulus E, in core and aggregate limestone samples from Kansas through the investigation and assessment of mineralogical and petrophysical variables. The main objectives of this study were to: (1) assess E in relation to mineralogical, petrophysical, and scale-dependent variability in Kansas limestone and (2) develop predictive models for E. For these purposes, we collected 29 1-inch and 28 2-inch limestone samples and measured E using uniaxial experiments under dry and saturated conditions. We present regression-based models in combination with decision trees that allow for the estimation of E based on water content θ and quartz content for saturated limestone samples. By comprehensively examining the geomechanical, petrophysical, and mineralogical properties of Kansas limestone cores, this study facilitates their utilization and suitability as aggregates in concrete production and various construction applications for the Kansas Department of Transportation (KDOT).
Keywords: Young's modulus; Limestone; Aggregates; Uniaxial compression